Feedlot performance and rumen morphometrics of Nellore cattle adapted to high-concentrate diets over periods of 6, 9, 14 and 21 days - Estevam, D. D. [UNESP]; Pereira, I. C. [UNESP]; Rigueiro, A. L.N. [UNESP]; Perdigão, A. [UNESP]; Da Costa, C. F. [UNESP]; Rizzieri, R. A. [UNESP]; Pereira, M. C.S. [UNESP]; Martins, C. L. [UNESP]; Millen, D. D. [UNESP]; Arrigoni, M. D.B. [UNESP] (Elsevier, 2020)
The energy content of finishing diets offered to feedlot cattle may vary across countries. We assumed that the lower is the energy content of the finishing diet, the shorter can be the adaptation period to high-concentrate diets without negatively impacting rumen health while still improving feedlot performance. This study was designed to determine the effects of adaptation periods of 6, 9, 14 and 21 days on feedlot performance, feeding behaviour, blood gas profile, carcass characteristics and rumen morphometrics of Nellore cattle. The experiment was designed as a completely randomised block, replicated 6 times, in which 96 20-month-old yearling Nellore bulls (391.1 ± 30.9 kg) were fed in 24 pens (4 animals/pen) according to the adaptation period adopted: 6, 9, 14 or 21 days. The adaptation diets contained 70%, 75% and 80.5% concentrate, and the finishing diet contained 86% concentrate. After adaptation, one animal per pen was slaughtered (n = 24) for rumen morphometric evaluations and the remaining 72 animals were harvested after 88 days on feed. Orthogonal contrasts were used to assess linear, quadratic and cubic relationships between days of adaptation and the dependent variable. Overall, as days of adaptation increased, final BW (P = 0.06), average daily gain (ADG) (P = 0.07), hot carcass weight (P = 0.04) and gain to feed ratio (G: F) (P = 0.07) were affected quadratically, in which yearling bulls adapted by 14 days presented greater final BW, ADG, hot carcass weight and improved G: F. No significant (P > 0.10) days of adaptation effect was observed for any of feeding behaviour variables. As days of adaptation increased, the absorptive surface area of the rumen was affected cubically, where yearling bulls adapted by 14 days presented greater absorptive surface area (P = 0.03). Thus, Nellore yearling bulls should be adapted by 14 days because it led to improved feedlot performance and greater development of rumen epithelium without increasing rumenitis scores.
Keywords: Bos indicus; gain; high-energy; papillae; transition